ASSESSMENT OF THE INFLUENCE OF OVERWEIGHT AND OBESITY ON THE DEVELOPMENT OF PREHYPERTENSION AND HYPERTENSION IN CHILDREN AGED 6-15 - Jandric-Kocic, Marijana (HEALTH CARE, 2021)
Introduction/Aim: 41 million children under the age of 5 and 340 million children and adolescents aged 5 to 19 are overweight or obese. Obesity in children and adolescents is the most important predictor of high blood pressure. The aim of the study was to examine the incidence of overweight and obesity in primary school children aged 6 to 15 years, as well as to examine the incidence of prehypertension and hypertension in children who were overweight and obese. Method: The study included 85 of 86 children from the Primary School „Krupa na Uni“. Data were collected with the help of a questionnaire, while body weight and blood pressure were measured. The chi-square test and t-test were used for the statistical analysis of data. Results: The cross-sectional study included 85 children, 45 (52.9%) boys and 40 (47.1%) girls with an average age of 10.87 ± 2.70 years. Normal weight was found in 54 (63.5%) subjects, underweight in 12 (14.1%), overweight in 5 (5.9%), and obesity in 14 (16.5%). 76 (89.4%) subjects had normal blood pressure values, 5 (5.9%) pre-hypertensive state, and 4 (4.7%) arterial hypertension. There was no significant difference between younger and older children regarding their nutritional status (p=0.477) and blood pressure levels (p=0.453). Children who were overweight and obese had prehypertension and hypertension significantly more often (p˂0.001). Conclusion: Every fifth child was overweight or obese, while prehypertension or hypertension were found in every tenth child. The timely change of diet and physical activity could contribute to the regulation of body weight and the regulation of blood pressure, as well.